Turkish Neonatal Society guideline on prevention and management of bronchopulmonary dysplasia - Arsan, Saadet; Korkmaz, Ayse; Oguz, Suna (TURKISH PEDIATRICS ASSOC, 2018)
Scientific and technological advances in perinatology and neonatology have led to an increased rate of survival and decreased incidences of various neonatal morbidities. However, the incidence of bronchopulmonary dysplasia has remained almost the same for years in very-low-birth-weight preterm infants. Although bronchopulmonary dysplasia is the leading cause of chronic respiratory morbidity in small preterms, no substantial improvement has been achieved in prevention and treatment strategies to date. Currently, postnatal very-low-dose corticosteroids, caffeine, and vitamin A seem to be the drugs of choice, and stem cell therapy appears to be the most promising treatment modality for the future. In this guideline, which was prepared by the Turkish Neonatal Society, recent evidence-based recommendations for the prevention and treatment of bronchopulmonary dysplasia are summarized.
Keywords: Bronchopulmonary dysplasia; guideline; prevention; treatment